The elements of modern architecture understanding contemporary buildings - Radford, Antony; Morkoç, Selen B. (Selen Bahriye); Srivastava, Amit (Architect) (New York Thames & Hudson, 2014)
"Dissects fifty of the world's modern masterpieces, constructed from 1950 to the present, through specially commissioned freehand drawings that reveal the principles and details of what makes a building meaningful and enduring. Starting from its site, each work is analyzed through its surroundings, use of natural light, volume and massing; its program and circulation; and its details, fenestration and ornamentation, showing the reader how the building works as a cohesive whole." --Back Cover.
Introduction -- Sarabhai House, 1951-55, Ahmedabad, India / Le Corbusier -- Canova Museum, 1955-57, Possagno, Treviso, Italy / Carlo Scarpa -- Sydney Opera House, 1957-73, Sidney Australia / Jorn Ulzon -- Solomon R. Guggenheim Museum, 1943-59, New York, USA / Frank Llyod Wright -- Leicester Engineering Building, 1959-63, Leicester, England /Stirling & Gowan --Salk Institute for Biological Studies, 1959-66, La Jolla, California, USA / Louis Kahn -- Louisiana Musuem of Modern Art, 1956-58, Humlebaek, Denmark / Jorgen Bo and Wilheim Wohlert -- Yoyogi National Gymnasium, 1961-64, Tokyo, Japan / Kenzo Tange -- Seinajoki Town Hall / 1958-65, Seinajoki, Ostrobothnia, Finland / Alvar Aalto -- St Mary's Cathedral, 1961-64, Tokyo, Japan / Kenzo Tange -- Hedmark Museum, 1963-74, Ahmedabad, India / Louis Kahn -- Bagsvaerd Church, 1974-76, Bagsvaerd, Copenhagen, Denmark / Jorn Utzon -- Milan House, 1972-75, Cidade Jardim, Sao Paolo, Brazil / Marcos Acayaba Arquitectos -- HSBC Office Building, 1979-84, Stuttgart, Germany / James Stirling, Michael Wilford & Associates --House at Martha's Vineyard, 1984-88 , Martha's Vineyard, Massachussets, USA / Steven Holl Architects -- Church on the Water, 1985-88, Tomamu, Hokkaido, Japan / Tadao Ando Architect & Associates -- Llyod's of London Office Building, 1978-86, London, England / Richard Rogers -- Arab World Institute, 1981-87, Paris, France / Jean Nouvel -- Barcelona Museum of Contemporary Art, 1987-95, Barcelona, Spain / Richard Meier -- Vitra Fire Station, 1990-93, Weil am Rhein, Germany / Zaha Hadid -- Lord's Madia Centre, 1994-99, London England / Future Systems -- Menara UMNO, 1995-98, Penang, Malysia / Kenneth Yeang, T.R. Hamzah & Yeang -- Dancing Building, 1992-96, Prague, Czech Republic / Frank O. Gehry & Associates, Vlado Mluniac -- Eastgate, 1991-96, Harare, Zimbabwe / Pearce Partnership -- Thermal Baths in Vals, 1986-96, Vals, Switzerland / Peter Zumthor -- Guggenheim Museum Bilbao, 1991-97, Bilbao, Spain / Frank O. Gehry & Associates -- ESO HOtel, 1998-2002, Cerro Paranal, Chile / Auer+Weber -- Arthur and Yvonne Boyd Education Centre, 1996-99, New South Wales, Australia / Murcutt Lewin Lark -- Jewis Museum Berlin, 1988-99, Berlin Germany / Daniel Libeskin -- Quadracci Pavilion, 1994-2001, Milwaukee, Wisconsin, USA / Santiago Caltrava -- B2 House, 199-2001, Buyukhusun, Ayvacik, Turkey / Han Tumertekin -- Caixa Forum, 2001-03, Madrid, Spain / Herzog de Meuron -- New Museum, 2001-07, New York, USA / SANAA (Kazuyo Sejima and Ryue Nishizawa -- Scottish Parliament Building, 1998-2002, Edinburgh, Scoland / EMBT, RMJM -- Yokohama Port Terminal, 1995-2002, Yokohama, Japan / Foreign Office Architects-- Modern Art Museum of Forth Worth, 1996-2002, Fort Worth, Texas, USA / Tadao Ando Architect & Associates -- Kunsthaus Graz, 2000-3, Graz, Austria / Spacelab Cook Fournier, ARGE Kunsthaus --Linked Hybrid, 2003-9, Beijing, China / Steven Holl Architects -- Santa Caterina Market, 1997-2005, Barcelona, Spain / EMBT -- Southern Cross Station, 2001-6, Melbourne, Australia / Grimshaw Architects, Jackson Architecture -- Meiso no Mori Crematorium, 2004-9, Kakamigahara, Gifu, Japan / Tokyo Ito & Associates -- Civil Justice Center, 2001-7, Manchester, England / Denton Corker Marshall -- Green School, 2005-7,Bandang, Bali, Indonesia / Green School PT Bambu -- Mimesis Museum, 2007-9, Paju Book City, Republic of Korea / Alvaro Siza, Castanheira & Bastai, Jun Sung Kim -- Julliard School & Alice Tully Hall, 2003-9, New ?York, USA / Diller Scofidio + Renfro, FXFOWLE --41 Cooper Square, 2004-9, New York, USA / Morphosis Architects --Oslo Opera House, 2002-8, Oslo, Norway / Snohetta --MAXXI, 1998-2009, Rome, Italy MAXXI Zaha HAdid.)
Includes bibliographical references (pages 333-338) and index.
Keywords: Architecture, Modern -- 20th century -- Themes, motives; Architecture, Modern -- 21st century -- Themes, motives; Architecture -- Details